The Potential of Religious Education in Preventing Suicide among Children and Adolescents in Poland: Theoretical Analysis and Implications for Pre-suicidal Prevention - Chrostowski, Mariusz (Paedagogia Christiana, 2023)
The second leading cause of death in Poland is suicide committed by young people aged 7 to 18 years. It appears that not enough is being done in the Polish Catholic community to protect the young generation from self-destructive behaviour. The preventive powers of Christianity and Religious Education in this area remain largely unutilised. This article not only highlights the primary causes and various aspects of suicide among children and youth in Poland, but it also signals (on the level of theoretical considerations) the ‘pro-life potential’ that lies in Religious Education. The implications related to the teaching of religion are presented as a starting point for the systemic and planned religious-pedagogical and pastoral activities for suicide prevention, as well as mental and spiritual support of students at risk of suicide.